2016
DOI: 10.3233/jad-160096
|View full text |Cite
|
Sign up to set email alerts
|

Gypenoside XVII Enhances Lysosome Biogenesis and Autophagy Flux and Accelerates Autophagic Clearance of Amyloid-β through TFEB Activation

Abstract: A strategy for activating transcription factor EB (TFEB) to restore autophagy flux may provide neuroprotection against Alzheimer's disease. Our previous study reported that gypenoside XVII (GP-17), which is a major saponin abundant in ginseng and Panax notoginseng, ameliorated amyloid-β (Aβ)25-35-induced apoptosis in PC12 cells by regulating autophagy. In the present study, we aimed to determine whether GP-17 has neuroprotective effects on PC12 cells expressing the Swedish mutant of APP695 (APP695swe) and APP/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…Although ERs is pathways upstream of PI3K [14], the inhibition effect of ICI182780 is worse than LY294002. That’s because GP-17 had other protection mechanism, so the inhibition of ERs downstream targets could result in more effective inhibition against GP-17 protection of HUVECs [36]. What’s more, LDH release is a consequence of damage to cellular integrity during apoptosis, which can indirectly reflect cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Although ERs is pathways upstream of PI3K [14], the inhibition effect of ICI182780 is worse than LY294002. That’s because GP-17 had other protection mechanism, so the inhibition of ERs downstream targets could result in more effective inhibition against GP-17 protection of HUVECs [36]. What’s more, LDH release is a consequence of damage to cellular integrity during apoptosis, which can indirectly reflect cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…48 Furthermore, gypenoside XVII is a promising candidate for the prevention of AD due to facilitation of the autophagy-dependent removal of Aβ through TFEB activation in cellular and rodent models of AD. 68 Gypenoside XVII could also attenuate Aβ25-35induced parallel autophagic and apoptotic cell death through the estrogen receptor-dependent activation of Nrf2/ARE pathways. 69…”
Section: Neurodegenerative Disordersmentioning
confidence: 98%
“…A study also reported the potential of GP-17, a novel phytoestrogen isolated from ginseng, in the clearing of A␤ in vivo and in vitro in the AD mouse models, Swedish mutant of APP695 (APP695swe) and APP/PS1. The neuroprotective effect was due to the autophagy-based elimination of A␤ due to the activation of transcription factor EB responsible for lysosome biogenesis [100]. It is useful in the inhibition of formation of A␤, stimulation of soluble A␤PP␣ formation, anti-inflammation, anti-apoptosis, decreasing oxidation stress, and enhancing CNS cholinergic function to counter impairments and implications associated with AD [101,102].…”
Section: Panax Ginseng (Ginseng)mentioning
confidence: 99%